Oxr1 and Ncoa7 regulate V-ATPase to achieve optimal pH for glycosylation within the Golgi apparatus and trans-Golgi network - Shin-ichiro Yoshimura; Tomoaki Sobajima; Masataka Kunii; Akihiro Harada (Proceedings of the National Academy of Sciences, 2025)
Maintenance of pH within membranous organelles is crucial for cellular processes such as posttranslational modifications, ligand–receptor interactions, and proteostasis. The precise mechanisms that determine the luminal pH of each organelle are not fully understood. This study investigated the mechanisms that regulate luminal pH to ensure optimal enzymatic activity. We identified Oxr1 and its paralog Ncoa7, which regulate the vacuolar-type proton pump ATPase (V-ATPase) at the Golgi apparatus and trans-Golgi network (TGN). Oxr1 and Ncoa7 were predominantly localized at the Golgi and TGN membranes, dependent on their binding to various GTP-bound Rab proteins. In vitro experiments using purified recombinant proteins indicated that Oxr1 and Ncoa7 directly bind to the catalytic subunit of V-ATPase, inhibiting its ATP hydrolytic activity via their TLDc domains. We observed significant acidification of the Golgi/TGN lumen in Oxr1- and Ncoa7-depleted cells. Lectin blot analysis demonstrated that depletion of Oxr1 and Ncoa7 led to a defect in protein glycosylation, a major enzymatic posttranslational modification in the Golgi and TGN. Furthermore, depletion of Oxr1 and Ncoa7, along with drug-induced inhibition of glycosylation, increased lysosomal pH and sensitivity to silicon dioxide-induced membrane damage. This apparent lysosomal dysfunction suggested that, in addition to the Golgi and TGN, Oxr1 and Ncoa7 also contribute to the integrity of other organelles. Our findings indicate that Oxr1 and Ncoa7 protect the Golgi and TGN lumen from excess acidification by inhibiting V-ATPase activity and providing an optimal environment for enzymatic activity in the Golgi and TGN.